Descriptive study of anxiety among chronic kidney disease patients underwent hemodialysis: Pilot study - R Rokhmat; Achmad Zulfa Juniarto; Chandra Bagus Ropyanto (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Chronic kidney disease is a kidney organ disease that cannot be cured, has been suffering for the whole life of the patient and must depend on a kidney function replacement device to maintain the sufferer life. Patients who have experienced chronic kidney disease undergoing hemodialysis are difficult to cure and become a major problem for the world, especially the problem of the treatment costs are relatively expensive. Health conditions that are experienced is a crisis situation that can cause psychological disorders. Psychological problems which often arise in patients with chronic kidney disease is anxiety. This study aims to determine the anxiety of chronic kidney patients undergoing hemodialysis at Batang Regional Public Hospital (RSUD). This research type is qualitative research with a descriptive method of phenomenology. The subjects in this study were patients with chronic kidney disease who underwent hemodialysis at Batang Regional Public Hospital (RSUD). The technique used in taking participants using purposive sampling with the number of 5 participants. Data collection techniques in this study used structured interviews about anxiety in 3 aspects, namely physiological, psychological and affective aspects. Data analysis was performed by data reduction, triangulation and drawing conclusions. The results obtained in this study there are 3 aspects of anxiety experienced by participant namely physiological, psychological, and affective aspects. In the physiological aspects of patients complaining that it was difficult to sleep, in the psycho-psychological aspect, the patient still felt afraid of the affective aspects of the patient complaining of decreased patience and tension before hemodialysis.Studi deskriptif kecemasan pasien penyakit ginjal kronik yang menjalani hemodialisa: Pilot studyAbstrak: Penyakit ginjal kronis merupakan penyakit pada organ ginjal yang tidak dapat disembuhkan, diderita seumur hidup pasien dan harus bergantung dengan alat pengganti fungsi ginjal guna mempertahankan kehidupan penderitanya. Pasien yang sudah mengalami penyakit ginjal kronis yang menjalani hemodialisa sulit untuk disembuhkan dan menjadi masalah besar bagi dunia, terutama masalah biaya perawatan dan pengobatannya yang relatif mahal. Kondisi kesehatan yang di alami merupakan sebuah krisis situasi yang dapat menyebabkan gangguan psikis dan psikologis. Permasalahan psikologis yang sering muncul pada pasien penyakit ginjal kronis adalah kecemasan. Penelitian ini bertujuan untuk mengetahui kecemasan pasien ginjal kronik yang menjalani hemodialisa di RSUD Batang. Jenis penelitian yang digunakan adalah penelitian kualitatif dengan metode deskriptif femomenologi. Subjek dalam penelitian ini adalah pasien penyakit ginjal kronik yang menjalani hemodialisa di RSUD Batang. Teknik yang digunakan dalam pengambilan partisipan menggunakan purposive sampling dengan jumlah partisipan adalah 5 partisipan. Teknik pengambilan data dalam penelitian ini menggunakan wawancara terstruktur tentang kecemasan dalam 3 aspek yaitu aspek fisiologis, psikologis dan afektif. Analisa data dilakukan dengan melakukan reduksi data, triangulasi dan menarik kesimpulan. Hasil yang diperoleh dalam penelitian ini ada 3 aspek kecemasan yang dialami partispan yaitu aspek fisiologis, piskologis, dan aspek afektif. Pada aspek fisiologis pasien mengeluhkan sulit untuk tidur, pada aspek psikoogispasien masih merasa takut pada aspek afektif pasien mengeluhkan penurunan kesabaran dan tegang sebelum tindakan hemodialisa.